Interview with Prof. Hiroshi Fukuda: the 50-year history of boron neutron capture therapy - Fan, Wei-En (Therapeutic Radiology and Oncology, 2019)
The 18th International Congress on Neutron Capture Therapy (ICNCT) was successfully held in Taipei, Taiwan from October 28 to November 2. Researchers came from different countries, such as Japan, USA, Italy, Argentina, Germany, Finland, etc. to attend this grand meeting. The gathering of researchers in the fields of radiology, chemistry, physics, nuclear medicine and pathology has enriched and stimulated discussion during the meeting.